Strategi Komunikasi Media Sosial untuk Meningkatkan Brand Image Hammerstoutdenim - Akmal, Gian Maulana; Muhtadi, Asep Saeful; Darsono, Dono (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
This study aims to find out how the social media communication strategy to improve Hammerstoutdenim's brand image on Instagram @hammerstoutdenim through the Circular Model of SoMe for Social Communication was developed by Regina Luttrell. This research was carried out using a qualiative descriptive method with primary and secondary data through data collection techniques, namely in-depth interviews, observations, and documentation studies. The results of the research obtained are that the Hammerstoutdenim brand is appropriate in implementing a social media communication strategy to improve brand image through Instagram in line with the Circular Model of SoMe for Social Communication, with the following indicators: 1) share: determine the target audience, formulate content to be shared on Instagram and make adjustments to the time in sharing content; 2) optimize: create content descriptions and adapt content to special days; 3) manage: create content by referring to content or guide lines and create content schedules; 4) engage: fast response and repost followers content.